HUBUNGAN SIKAP KERJA DENGAN KELELAHAN KERJA PADA PEKERJA LAUNDRY DI KECAMATAN PURWOKERTO UTARA KABUPATEN BANYUMAS - Gandung Kartika Tri Nugroho; Nur Ulfah; Siti Harwanti (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2015)
Fatigue could significantly degrade performance and increase the error rate of employment. Moreover, fatigue contributed significantly to the occurrence of occupational accidents. Fatigue is characterized by weakening employment of labor in doing the work or activities. Fatigue was influenced by several factors, both internal and external factors. Working attitude was one of the internal factors. The purpose of this study was to determine the relationship of working attitude to the occurrence of working fatigue of workers at Laundry on North Purwokerto district in Banyumas. The study was conducted using observational approach by cross sectional research design with the study sample amounted to 150 respondents consisted of 30 samples in 5 section laundry. Analyses of data used are univariate and bivariate analysis(chi square). Based on five section working attitude studied are weighing, washing, drying, ironing and packaging, factor associated with work exhausted is the ironing section. The factor that are not associated with work exhausted is weighing, washing, drying and packaging. As a suggestion to reduce the occurrence of fatigue, giving education of ergonomic attitude on laundry workers and more resting time, and giving ergonomic design means working as an ergonomic desk chair for ironing section.